Absence of Musculocutaneous Nerve: A Rare Anatomical Variation - Giridhar M Kanthi,; Sunitha Valsan, (International Journal of Ayurveda and Pharma Research, 2022)
Neural variation of the brachium constitutes a significant anatomical and clinical entity. The absence of Musculocutaneous Nerve is occasional in humans and accordingly there may be unforeseen clinical implication regarding the atypical innervations of musculature otherwise supplied by the Musculocutaneous Nerve. The present study is an absence of Musculocutaneous nerve observed during our routine educational dissection, where the lateral cord of brachial plexus took over the area of supply of Musculocutaneous Nerve by giving both the muscular and sensory branches. Knowledge of these variations is important in surgeries and during the administration of regional anaesthesia near shoulder joint and upper arm.